Transgenic Soybeans Expressing Phosphatidylinositol-3-Phosphate-Binding Proteins Show Enhanced Resistance Against the Oomycete Pathogen Phytophthora sojae - Helliwell, Emily E.; Lafayette, Peter; Kronmiller, Brent N.; Arredondo, Felipe; Duquette, Madeleine; Co, Anna; Vega-Arreguin, Julio; Porter, Stephanie S.; Borrego, Eli J.; Kolomiets, Michael V.; Parrott, Wayne A.; Tyler, Brett M. (Frontiers in Microbiology, 2022)
Oomycete and fungal pathogens cause billions of dollars of damage to crops worldwide annually. Therefore, there remains a need for broad spectrum resistance genes, especially ones that target pathogens but do not interfere with colonization by beneficial microbes. Motivated by evidence suggesting that phosphatidylinositol-3-phosphate (PI3P) may be involved in the delivery of some oomycete and fungal virulence effector proteins, we created stable transgenic soybean plants that express and secrete two different PI3P-binding proteins, GmPH1 and VAM7, in an effort to interfere with effector delivery and confer resistance. Soybean plants expressing the two PI3P-binding proteins exhibited reduced infection by the oomycete pathogen Phytophthora sojae compared to control lines. Measurements of nodulation by nitrogen-fixing mutualistic bacterium Bradyrhizobium japonicum, which does not produce PI3P, revealed that the two lines with the highest levels of GmPH1 transcripts exhibited reductions in nodulation and in benefits from nodulation. Transcriptome and plant hormone measurements were made of soybean lines with the highest transcript levels of GmPH1 and VAM7, as well as controls, following P. sojae- or mock-inoculation. The results revealed increased levels of infection-associated transcripts in the transgenic lines, compared to controls, even prior to P. sojae infection, suggesting that the plants were primed for increased defense. The lines with reduced nodulation exhibited elevated levels of jasmonate-isoleucine and of transcripts of a JAR1 ortholog encoding jasmonate-isoleucine synthetase. However, lines expressing VAM7 transgenes exhibited normal nodulation and no increases in jasmonate-isoleucine. Overall, together with previously published data from cacao and from P. sojae transformants, the data suggest that secretion of PI3P-binding proteins may confer disease resistance through a variety of mechanisms.